Upgrading small wastewater treatment plants with the sequencing batch biofilter granular reactor technology: Techno-economic and environmental assessment. (1st April 2017) - Di Iaconi, Claudio; Del Moro, Guido; Bertanza, Giorgio; Canato, Matteo; Laera, Giuseppe; Heimersson, Sara; Svanström, Magdalena
Abstract: This paper is aimed at evaluating, from a techno-economic and environmental point of view, the performance of an existing wastewater treatment plant in which the traditional biological section is upgraded with an innovative Sequencing Batch Biofilter Granular Reactor. Two scenarios were simulated in order to model and assess the performances of conventional (CAS, Conventional Activated Sludge) and innovative solutions, based on mass balances, techno-economic evaluation and environmental assessment. The results showed that converting the activated sludge process into an SBBGR allows to achieve a drastic reduction in sludge production (up to 75% as volatile suspended solids). Furthermore, the secondary sedimentation and sludge stabilization units can be dismissed, reducing the area requirement (up to 50%). The technical assessment is mainly positive, with the electric energy consumption being the only critical item. The higher energy demand of the upgraded plant (about 25% more than the conventional treatment) is mainly associated with the recycle flow in the SBBGR system. Although the economic sustainability of the upgraded plant depends on local conditions, it can be considered to be likely favourable: sludge disposal and materials & reagents costs, together with the investment for plant reconstruction are those items that should be carefully evaluated before upgrading the CAS plant with SBBGR technology. The environmental assessment shows also mostly positive results, although it points to the increased phosphorus concentration in the effluent as a potentially critical issue and it highlights the electricity use and the increased nitrous oxide generation as other matters that need to be carefully checked in real case application. Highlights: Sustainability of an upgrade of a conventional WWTP with a SBBGR system was evaluated. The technical assessment of the upgrading is mainly positive. Also the economic assessment is mainly positive. The economic sustainability of the upgrading depends on local conditions. The environmental assessment shows positive results, although the increased phosphorus concentration can be a potential issue.